การปฏิบัติงานของคณะกรรมการดำเนินงานศูนย์พลังแผ่นดินเอาชนะยาเสพติด จังหวัดเลย - โคตรณรงค์, พันตรีสุรชาญ (วารสารศรีล้านช้างปริทรรศน์; Vol 6 No 2 (2020): วารสารศรีล้านช้างปริทรรศน์ ปีที่ 6 ฉบับที่ 2 (กรกฏาคม - ธันวาคม 2563), 2020)
บทความวิจัยนี้มีวัตถุประสงค์เพื่อ (1) ศึกษาการปฏิบัติงานของคณะกรรมการดำเนินงานศูนย์พลังแผ่นดินเอาชนะยาเสพติด จังหวัดเลย (2) เปรียบเทียบการปฏิบัติงานของคณะกรรมการดำเนินงานศูนย์พลังแผ่นดินเอาชนะยาเสพติด จังหวัดเลย ที่มี อายุ ระดับการศึกษาและรายได้ต่อเดือนแตกต่างกัน และ (3) ศึกษาปัญหาและข้อเสนอแนะเกี่ยวกับการปฏิบัติงานของคณะกรรมการดำเนินงานศูนย์พลังแผ่นดินเอาชนะยาเสพติด จังหวัดเลย กลุ่มตัวอย่างที่ใช้ในการศึกษา คือ กรรมการและอนุกรรมการศูนย์ปฏิบัติการพลังแผ่นดินเอาชนะยาเสพติดจังหวัดเลย (ศพส. จ.เลย) ได้ใช้สูตรในการคำนวณหาขนาดกลุ่มตัวอย่างของทาโร ยามาเน่ (Taro Yamane) ได้กลุ่มตัวอย่าง จำนวน 136 คน เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูลครั้งนี้ คือ แบบสอบถาม มีลักษณะเป็นแบบมาตราส่วนประมาณค่า (Rating Scale) การวิเคราะห์ข้อมูล โดยใช้ค่าความถี่ ค่าร้อยละ ค่าเฉลี่ย (Mean) ค่าส่วนเบี่ยงเบนมาตรฐาน (Standard Deviation) ค่าที t - test และค่าความแปรปรวนทางเดียว (One-way ANOVA) หากพบความแตกต่างจะทดสอบเป็นรายคู่ด้วยวิธีการของ เชฟเฟ่ (Scheffe’s Method) โดยมีค่านัยสำคัญที่ 0.05             ผลการวิจัยพบว่า             1) คณะกรรมการและอนุกรรมการศูนย์ปฏิบัติการพลังแผ่นดินเอาชนะยาเสพติดจังหวัดเลย (ศพส. จ.เลย) เห็นว่าการปฏิบัติงานของศูนย์ปฏิบัติการพลังแผ่นดินเอาชนะยาเสพติดจังหวัดเลย โดยรวมทั้ง 4 ด้าน อยู่ในระดับมาก และเมื่อพิจารณารายด้าน พบว่า ด้านที่มีค่าเฉลี่ยมากที่สุด คือ ด้านนโยบาย รองลงมาได้แก่ ด้านแผนงาน และด้านการปฏิบัติตามนโยบาย ส่วนด้านที่มีค่าเฉลี่ยน้อยที่สุด คือ ด้านบริการจัดการ             2) ผลการเปรียบเทียบ พบว่า คณะกรรมการและอนุกรรมการศูนย์ปฏิบัติการพลังแผ่นดินเอาชนะยาเสพติดจังหวัดเลย (ศพส. จ.เลย) ที่มีอายุและรายได้ต่อเดือนต่างกันมีความคิดเห็นต่อการปฏิบัติงานของคณะกรรมการดำเนินงานในศูนย์ปฏิบัติการพลังแผ่นดินเอาชนะยาเสพติดจังหวัดเลย โดยรวมทั้ง 4 ด้าน แตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับนัยสำคัญ .05 ส่วนคณะกรรมการและอนุกรรมการศูนย์ปฏิบัติการพลังแผ่นดินเอาชนะยาเสพติดจังหวัดเลย (ศพส. จ.เลย) ที่มีระดับการศึกษาต่างกันมีความคิดเห็นต่อการปฏิบัติงานของคณะกรรมการดำเนินงานในศูนย์ปฏิบัติการพลังแผ่นดินเอาชนะยาเสพติดจังหวัดเลย โดยรวมทั้ง 4 ด้าน ไม่แตกต่างกัน             3) ปัญหาการปฏิบัติงานของคณะกรรมการดำเนินงานในศูนย์ปฏิบัติการพลังแผ่นดินเอาชนะยาเสพติดจังหวัดเลย ส่วนใหญ่มีข้อเสนอมากที่สุดคือ นโยบายการทำงานของแต่ละหน่วยงานไม่มีความสอดคล้องกัน รองลงมาได้แก่ การค้นหากลุ่มเป้าหมาย ไม่มีการคัดกรองโดย เจ้าหน้าที่สาธารณะสุข จึงทำให้ไม่ได้คัดแยกกลุ่ม เมื่อมารวมกันทำให้เกิดการสร้างเครือข่าย และน้อยที่สุด การขาดการมีส่วนร่วมของหน่วยงานที่เกี่ยวข้อง             ข้อเสนอแนะการปฏิบัติงานของคณะกรรมการดำเนินงานในศูนย์ปฏิบัติการพลังแผ่นดินเอาชนะยาเสพติดจังหวัดเลย ส่วนใหญ่มีข้อเสนอมากที่สุดคือ แก้ไขระเบียบให้เกิดความคล่องตัว รองลงมาได้แก่ ควรส่งต่อหน่วยงานที่เกี่ยวข้อง เช่น สาธารณสุข หรือ องค์การบริหารส่วนตำบล/เทศบาล และน้อยที่สุด จัดให้มีการอบรมให้ความรู้ด้านยุทธวิธี             The objectives of the research article were (1) to study performance of action committee in operation center of land power for narcotic drug suppression of Loei province, (2) to compare performance of action committee with the difference in age, educational level and monthly income in operation center of land power for narcotic drug suppression of Loei province, and (3) to study problems and suggestion about performance of action committee in operation center of land power for narcotic drug suppression of Loei province. The sample group used in this study was the committee and sub-committee in operation center of land power for narcotic drug suppression of Loei province. The sample size was determined by formula of Taro Yamane and there were 136 people selected as the sample group. The research instrument used in collecting data was the questionnaire with rating scale form. The data were analyzed by frequency, percentage, mean, standard deviation, t-test testing, and one-way test of variance (One-way ANOVA). If there was statistically significant difference at 0.05, there would be paired different testing of average with Scheffe’s method.             The results were found that’s:             1) The committee and sub-committee in operation center of land power for narcotic drug suppression of Loei province presented that the four sides of performance of operation center of land power for narcotic drug suppression of Loei province was at high level in overall and when each side was taken into consideration, the results were found that the policy side was at high level, the second was the plan and action according to the policy, and the lowest was the administration side             2) The results of comparison were found that the committee and sub-committee with the difference in age and monthly income in operation center of land power for narcotic drug suppression of Loei province had different opinion towards performance of action committee in operation center of land power for narcotic drug suppression of Loei province at statistically different significance of .05 level in all four sides. While the committee and sub-committee with the difference in educational level had no different opinion towards performance of action committee in operation center of land power for narcotic drug suppression of Loei province in all four sides.             3) The problems of performance of action committee in operation center of land power for narcotic drug suppression of Loei province were expressed as follows: most of the frequently was that the action policies of each organization were not related obviously, and the second was that the target group was chosen without action of public health officers; therefore, the target group was not divided into group appropriately. When they came into group, they had to make network, and the lowest was that there was no participation from the related organization.             The suggestions towards the performance of action committee in in operation center of land power for narcotic drug suppression of Loei province were as follows: the most frequency was the rules should be adjusted to be easily for working, the second was the adjusted rules should be transferred to the related organization such as public health or Tambol administrative organization, municipality, and the last was the knowledge on artifice should be taken into training properly.